"THE BOOK OF RUTH" IN JEWISH LITERATURE (THE BIBLICAL SUBTEXT IN THE NOVELS OF ISAAC BASHEVIS SINGER AND DAVID ALBAHARI) - Биљана С. Турањанин (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2011)
The work points out the significance of the biblical subtext, primarily "The Book of Ruth", for understanding the novel "Slave" Isaac Bashevis Singer and "Bait" David Albahari. Over motives Wandering Jew and Lord-savior, are underlined intertextual links that make these works more complex, open them to each other and make them members of the same literary family.